2000
DOI: 10.1128/iai.68.11.6147-6153.2000
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and Protein Processing Are Required for Presentation ofCryptococcus neoformansMitogen to T Lymphocytes

Abstract: In addition to eliciting antigen specific T-cell-mediated immunity, Cryptococcus neoformans possesses a mitogen (CnM) that activates naive T cells to proliferate. This mechanism of T-cell activation is accessory cell dependent and major histocompatibility complex unrestricted. CnM-induced T-cell proliferation correlates with internalization of the organism, suggesting that intracellular processing is required to liberate CnM prior to presentation to T cells. To determine whether phagocytosis and processing are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…It had been previously demonstrated that the lysosomal compartment and serine proteases were required for processing of C. neoformans (74). This raised the possibility that a leucine methyl ester (LME)-sensitive compartment might be required for processing of C. neoformans.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It had been previously demonstrated that the lysosomal compartment and serine proteases were required for processing of C. neoformans (74). This raised the possibility that a leucine methyl ester (LME)-sensitive compartment might be required for processing of C. neoformans.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously demonstrated that APC are required for T-cell responses to CnM (75) and that phagocytosis of C. neoformans is required for the APC to present CnM to T cells (73,74). To establish the type of cell that is the APC, blood mononuclear cells were separated based on their adherence properties, which have been used by other investigators to separate populations of APC (35,57,69).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful phagocytosis is required for effective CMI, and proliferation of lymphocytes in response to C. neoformans correlates with the magnitude of phagocytosis (46,47). Therefore, we hypothesized that impaired phagocytosis affects the host-pathogen interaction and alters the CMI.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, increased melanin activation of the complement system may have been responsible for the significantly enhanced opsonization of melanized nonencapsulated cells relative to that of nonmelanized nonencapsulated cells. Differences in the efficiency of phagocytosis of melanized and nonmelanized cells could translate into differences in the immune response since fungal cell ingestion can affect antigen presentation, cytokine production, dendritic cell activation, intracellular fungal growth, and macrophage cell viability (4,(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%